(untitled) (AYUSHDHARA, 2017)
Wound healing is a complex and dynamic process, with the wound environment changing with the improving health status of the individual. The knowledge of the physiology of the normal wound healing trajectory through the phases of haemostasis, inflammation, granulation and maturation and provides a framework for the understanding of basic principles of wound healing. Studies reveal that it is difficult to achieve the complete aim of wound management with a single drug. In the present study Manjisthadi taila is selected from Sushruta Samhita. It consists of Tila Taila, Manjistha, Haridra, Bharangi, Tutha, Hulhula, Lodhra, Haritaki, Madhuyasthi, Vidanga, Priyal, Talispatram, Kash, Chandan, Padamkesar, Tinduk, Padamakam, Renukabeej & Ksheeripatra. These drugs possess Vrana shodhana & Ropana properties. It was used topically in patients of Shudha vrana formed after cut through of ligated Ksharasutra in different cases like piles, fissure, excised cyst, excised pilonidal sinus & excised corn for three months or till complete healing whichever is earlier. It is a single blind clinical study where forty patients were selected & divided randomly into two groups of twenty patients each. Trial group patients wound were treated with dressing of Manjishtadi taila and control group patients wound were treated with Povidone-Iodine dressing. Manjisthadi taila reduces pain, burning sensation, swelling, tenderness, discharge, color & odour, it helps in gradual improvement of granulation tissue as compared to control group. Hence it can be speculated that Manjishtadi taila possess sufficient efficacy in Vrana shodhana & Vrana ropana without producing any deleterious effects.